1999
DOI: 10.1108/08876049910256186
|View full text |Cite
|
Sign up to set email alerts
|

Word‐of‐mouth communication in the service marketplace

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
210
2
23

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(239 citation statements)
references
References 36 publications
4
210
2
23
Order By: Relevance
“…Similar to product-related word-of-mouth, job-related word-of-mouth can vary with respect to its medium (e.g., face-to-face vs. internet), source (e.g., friend vs. acquaintance), motives (e.g., uncertainty reduction of the recipient vs. vengeance of the source), and valence (e.g., positive vs. negative; J. J. Brown & Reingen, 1987;Cable & Turban, 2001;Herr et al, 1991;Mangold et al, 1999;Smith & Vogt, 1995).…”
Section: Word-of-mouth As a Source Of Employment Informationmentioning
confidence: 99%
“…Similar to product-related word-of-mouth, job-related word-of-mouth can vary with respect to its medium (e.g., face-to-face vs. internet), source (e.g., friend vs. acquaintance), motives (e.g., uncertainty reduction of the recipient vs. vengeance of the source), and valence (e.g., positive vs. negative; J. J. Brown & Reingen, 1987;Cable & Turban, 2001;Herr et al, 1991;Mangold et al, 1999;Smith & Vogt, 1995).…”
Section: Word-of-mouth As a Source Of Employment Informationmentioning
confidence: 99%
“…Sundaram et al (1998) conducted 390 critical-incident interviews and identified four motives of consumers to actively spread positive WOM messages; namely, altruism, product involvement, self-enhancement, and helping the company. Mangold, Miller, and Brockway (1999) found that seekers' need for information far more likely initiated WOM communication compared to senders' satisfaction level or the marketing organization's promotional efforts. When consumers lack the ability to evaluate a buying decision before making a purchase, they are likely to request the experience of relatives and friends who have already used the product.…”
Section: Sender-initiated Wommentioning
confidence: 99%
“…Especially when individuals experience a high degree of uncertainty about a particular buying situation, they usually ask their friends for product opinions or even delegate the entire purchase decision to their friends (Aggarwal & Mazumdar, 2008). According to Mangold, Miller, and Brockway's (1999) study, the seeker initiated over 50% of the WOM incidents. However, it is somewhat surprising that little research examined the effect of WOM in this situation.…”
Section: Introductionmentioning
confidence: 99%
“…These include Mangold, Miller, and Brockway (1999), Bansal and Voyer (2000), and Harrison-Walker (2001). Haywood (1989) discusses the importance of managing WOM and puts forth guidelines for managers of service businesses.…”
Section: Overviewmentioning
confidence: 99%